Disease-modifying drugs in Alzheimer's disease - Ghezzi L; Scarpini E; Galimberti D (Dove Medical Press, 2013)
Laura Ghezzi, Elio Scarpini, Daniela Galimberti Neurology Unit, Department of Pathophysiology and Transplantation, University of Milan, Fondazione Cà Granda, IRCCS Ospedale Maggiore Policlinico, Milan, Italy Abstract: Alzheimer's disease (AD) is an age-dependent neurodegenerative disorder and the most common cause of dementia. The early stages of AD are characterized by short-term memory loss. Once the disease progresses, patients experience difficulties in sense of direction, oral communication, calculation, ability to learn, and cognitive thinking. The median duration of the disease is 10 years. The pathology is characterized by deposition of amyloid beta peptide (so-called senile plaques) and tau protein in the form of neurofibrillary tangles. Currently, two classes of drugs are licensed by the European Medicines Agency for the treatment of AD, ie, acetylcholinesterase inhibitors for mild to moderate AD, and memantine, an N-methyl-D-aspartate receptor antagonist, for moderate and severe AD. Treatment with acetylcholinesterase inhibitors or memantine aims at slowing progression and controlling symptoms, whereas drugs under development are intended to modify the pathologic steps leading to AD. Herein, we review the clinical features, pharmacologic properties, and cost-effectiveness of the available acetylcholinesterase inhibitors and memantine, and focus on disease-modifying drugs aiming to interfere with the amyloid beta peptide, including vaccination, passive immunization, and tau deposition. Keywords: Alzheimer's disease, acetylcholinesterase inhibitors, memantine, disease-modifying drugs, diagnosis, treatment